Barriers and enablers of women's academic careers in Pakistan. Issue 2 (3rd April 2019) - Fazal, Shawana; Naz, Sadaf; Khan, Muhammad Ilyas; Pedder, David
ABSTRACT: This qualitative study explores women academics' perspectives and experiences working in a Pakistani university regarding their careers and how these progress. This is located in a northern city in the Khyber Pakhtunkhwa province. Rich narrative accounts were sought from ten women academics, combining semi-structured and informant-style interviewing. Their accounts focused on their academic, professional and family lives. Thematic analysis of these revealed a range of experiences pertaining to their academic and career progression and included factors that enabled them to work and others that served as barriers. The former included sustained family support received from parents, siblings and spouses, while the latter included inequality of opportunities in a male-dominated work environment, balancing home and work responsibilities, and lack of workplace facilities. Most of these women found it challenging to maintain balance between their home and workplace responsibilities. Nevertheless, our informants reportedly refused to be overwhelmed by the challenges they faced; instead, they displayed a great deal of resilience and displayed a spirit of defiance, optimism and efficacy to deal with challenges at the workplace and in their homes.